Soil quality indexes in areas cultivated with banana in Panamá. - Villarreal-Núñez, José (2013)
The objective of this research was to obtain anindex that could serve as a useful tool for environmentalassessment and managing agricultural banana soils inPanama. The work was performed in five independent farmsfrom Alanje District and six properties belonging to theCooperative COOSEMUPAR in Baru (2005-2006). The soilsbelong to the orders Inceptisols (Andic Dystrudepts, Udichaplustepts and Dystric haplustepts) and Entisols (AndicUdifluvents). For the description of the indicators, four pitswere opened for each area of high and low productivity inthe band of fertilization of recently flowered banana plants.Biometric data were recorded of twenty banana plantsnear harvest. In addition, each site was measured for basicinfiltration, total weight of roots and sampled to determinethe physico-chemical and biological properties of the soil.In all farms high levels of Ca, Mg and K were detected,low concentrations of organic matter associated with lowbiological activity and low microbial biomass. In most farmsinfiltration was slow and degraded structures were present inthe lower horizons. The Minimum Data Set (MDS) that bestpredicted areas of high and low productivity was composedof the following indicators: percentage of sand, pH, Ca, K,organic matter, microbial respiration, mineralization rate andtotal weight of roots.